2017
DOI: 10.1037/cep0000134
|View full text |Cite
|
Sign up to set email alerts
|

Everyday attention.

Abstract: Understanding the basic mechanisms underlying attentional function using naturalistic stimuli, tasks, and/or settings is the focus of everyday attention research. Interest in everyday approaches to attention research has increased recently-arguably riding a more general wave of support for such considerations in experimental psychology. This special issue of the attempts to capture the emerging enthusiasm for studying everyday attention by bringing together work from a wide array of attentional domains (e.g., … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 35 publications
2
7
0
Order By: Relevance
“…Had we instead used a real human, it would have been unclear if any differences were due to the 3D context or the more complex social demands of the task. Replicating our task with a real 3D human would be of great interest, but for this investigation, we opted to incrementally “scale up” from the relative simplicity of more common computer-based tasks, minimizing the added difficulty of conducting 2 nd -person interactive research [ 35 ], or real-life “everyday attention” [ 36 ]. In fact, our own recent work illustrates the increases in sensitivity to gaze cues from the head and eyes that can be expected when scaling up from a virtual avatar to a virtual robot, a physically present robot, and finally, a physically present human [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Had we instead used a real human, it would have been unclear if any differences were due to the 3D context or the more complex social demands of the task. Replicating our task with a real 3D human would be of great interest, but for this investigation, we opted to incrementally “scale up” from the relative simplicity of more common computer-based tasks, minimizing the added difficulty of conducting 2 nd -person interactive research [ 35 ], or real-life “everyday attention” [ 36 ]. In fact, our own recent work illustrates the increases in sensitivity to gaze cues from the head and eyes that can be expected when scaling up from a virtual avatar to a virtual robot, a physically present robot, and finally, a physically present human [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…These distinct influences from the head and eyes work in parallel to oppose one another during perception of gaze in 3D faces [ 15 , 34 ]. Even beyond optical and perceptual considerations, judgments about social cues including gaze and social attention [ 35 , 36 ] take on additional significance, and even recruit distinct neural networks, when they are made in more embedded contexts in which the perceiver is an interactor rather than a spectator [ 37 ]. For these reasons, it is unclear whether knowledge about evaluations of 2D faces should generalize to 3D faces.…”
Section: Introductionmentioning
confidence: 99%
“…In keeping with Zigler's emphasis on the need to integrate developmental theory into the study of persons with ID (Burack et al 2020;Burack et al 2021), we attempt to frame the findings within recent conceptualisations of the development of attention (Ristic & Enns 2015a,b;Risko & Kingstone 2017). The term attention denotes the conglomeration of unconscious and conscious functions used to make sense of the deluge of information to which we are exposed in the dynamic, complex and ever-changing environment in which we live (Burack et al 2017).…”
Section: Advances In the Study Of Visual Attentionmentioning
confidence: 99%
“…Risko et al 2012;Brennan et al 2017;Hayward et al 2017). Thus, current advances in attention research include efforts to better replicate the contexts within which attention functions, thereby answering the call to address the now well-accepted reality that the development of attention is a product of complex person-environment interactions (Johnson & De Haan 2015;Ristic & Enns 2015a,b;Risko & Kingstone 2017).…”
Section: Advances In the Study Of Visual Attentionmentioning
confidence: 99%
“…As such, there are certainly shortcomings in transferring knowledge from computer-based visual search studies to real-world search behavior. The need to employ more naturalistic paradigms has recently been recognized in experimental psychology in general [5][6][7][8][9]. The fundamental discrepancy between classical laboratory research and real-world search behavior has been identified and can be addressed by two general approaches: (1) investigating real-world behavior and simplifying paradigms afterwards (cognitive ethology, [7]) and (2) extending classical visual search research by, for example, the employment of naturalistic scenes [10].…”
Section: Introductionmentioning
confidence: 99%